Local lattice relaxation around Tl substitutional impurities in a NaI(Tl) scintillator crystal. (December 2020) - Filipponi, A.; Profeta, G.; Di Marco, N.; Zema, V.; Schäffner, K.; Reindl, F.; Harfouche, M.; Trapananti, A.; Di Cicco, A.
Abstract: A Thallium (Tl) L 3 -edge x-ray absorption experiment was performed on a NaI(Tl) scintillation crystal at room temperature using fluorescence detection. The data analysis provides clear evidence for a ≃ 5 % average bond length expansion of the first shell I atoms surrounding the Tl impurities with respect to the Na-I crystallographic bond-length. Possible evidence for a slight expansion of the second and third shells is obtained. The data are compatible with a previous experiment performed at liquid nitrogen temperature considering thermal expansion. A critical review of existing theoretical predictions and density functional theory supercell calculations support present findings and suggest the opportunity to perform a high quality temperature dependent experiment.